Working Hours, Top Management Appointments, and Gender: Evidence from Linked Employer-Employee Data - Frederiksen, Anders; Kato, Takao; Smith, Nina (Journal of Labor Economics, 2026)
Using Danish registry data linked to the Labor Force Survey, we provide the first rigorous evidence with external validity on the hours-career nexus (positive association between hours and career success). Guided by three theories (human capital; rat race; tournament), we unpack the hours-career nexus through examining: the differential effect of hours in the present firm and elsewhere; hours relative to peers’ hours; standard vs. evening/night/weekend hours; and the importance of sustaining long hours. Supplemented by the time use survey, we show the gender gap in hours and career success is due mostly to gendered division of labor in household production.